2016
DOI: 10.1097/scs.0000000000002532
|View full text |Cite
|
Sign up to set email alerts
|

Metopic Craniosynostosis

Abstract: This study demonstrated an increasing incidence of metopic craniosynostosis over time, which ascended to the second most common type of synostosis in an analysis outside of an urban environment. In our study, male sex and multiple gestation were positively associated with an increased risk of metopic craniosynostosis. Prospective studies are needed to further delineate the evolving characteristics of this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…It is the result of premature metopic suture fusion and is the second most frequent type of single suture craniosynostosis. [1][2][3] The majority of trigonocephaly cases are sporadic but it can be syndromic in nature in around 35% of cases. 4 Trigonocephaly may have the most varied phenotypic presentation of the various craniosynostosis due to its limited role in frontal bone growth in infancy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is the result of premature metopic suture fusion and is the second most frequent type of single suture craniosynostosis. [1][2][3] The majority of trigonocephaly cases are sporadic but it can be syndromic in nature in around 35% of cases. 4 Trigonocephaly may have the most varied phenotypic presentation of the various craniosynostosis due to its limited role in frontal bone growth in infancy.…”
mentioning
confidence: 99%
“…1). It is the result of premature metopic suture fusion and is the second most frequent type of single suture craniosynostosis 1–3 . The majority of trigonocephaly cases are sporadic but it can be syndromic in nature in around 35% of cases 4 .…”
mentioning
confidence: 99%
“…Although this is a prospective study, it is limited by the relatively small cohort, especially in terms of sex distribution, which complies nevertheless to the generally expected sex distribution in many neurologic/neurosurgical disorders in children ( Bennett et al, 2016 , Masri et al, 2022 , Williams et al, 2019 ). Larger, ideally multicenter studies, should be conducted, to give general recommendations on the topic.…”
Section: Discussionmentioning
confidence: 85%
“…In an effort to add to the literature regarding CS rates in rural environments, a study at the University of Michigan Medical Center, representing the primary referral center of CS in Michigan, demonstrated a risk incidence of lambdoid, metopic, and sagittal CS that was similar to that of more urban surgical centers. 8 Despite the information available from multicenter and single-center studies, few studies have shown a statewide distribution of CS, especially in the southern United States. Multiple studies have presented the demographic characteristics of patients with CS, but to date, there has been no study representing the Mississippi population.…”
mentioning
confidence: 99%